Mitos Bunut Bolong di Desa Manggissari Kecamatan Pekutatan: Analisis Struktur dan Makna - Mita Manika Sari, Ni Putu; Sulibra, I Ketut Ngurah; Duana Sutika, I Nyoman (Humanis, 2019)
This research entitled "Myth Bunut Bolong Bolong in Manggissari Village Pekutatan Subdistrict Analysis of Structure and Meaning". Bunut Bolong myth in Manggissari Village Pekutatan District, analyzed by structural theory and semiotic theory. This study aims to describe the narrative structure found in the myth of bunut hole, and analyze the structure and meaning contained in the myth of bunut hole, Phase of data provision used method refer to assisted with technique note. It also used interview method assisted by recording technique and record technique, that is noting important things obtained from interview result. Furthermore, in the stage of data analysis used qualitative methods. In this stage also supported by analytic descriptive technique. At the presentation stage of data analysis, the method used is the informal method. Narrative structure that builds the myth of bunut hole in Manggissari Village, Pekutatan Sub-District there are five, that is incident, plot,Top of Form character, theme and background. On the myth of bunut hole there are events outside of reason happen, in the form of prohibitions or regulations that if violated will happen bad things. Meanings contained in the myth of bunut hole, namely (1) meaning tri hita karana, (2) religious meaning, and (3) the meaning of the ban.